(untitled) (Scientific journal of the Fergana State University, 2026)
In the context of global transformation, characterized by technological progress, economic shifts, and social changes, there is an increasing need to train specialists capable of engaging in innovative activities and implementing startup projects. This article analyzes pedagogical trends aimed at fostering students’ engagement in innovative and startup activities. The research focuses on identifying key educational approaches, methods, and technologies that contribute to developing students’ initiative, creativity, critical thinking, and entrepreneurial skills necessary for successful project implementation in a dynamically changing world.